Probiotic Properties of Bifidobacterium longum KABP042 and Pediococcus pentosaceus KABP041 Show Potential to Counteract Functional Gastrointestinal Disorders in an Observational Pilot Trial in Infants - Astó, Erola; Huedo, Pol; Altadill, Tatiana; Aguiló García, Meritxell; Sticco, Maura; Perez, Marta; Espadaler-Mazo, Jordi (Frontiers in Microbiology, 2022)
Functional gastrointestinal disorders (FGIDs) are a common concern during the first year of life. Recognized as gut-brain axis disorders by Rome IV criteria, FGIDs etiology is linked to altered gut-brain interaction, intestinal physiology, and microbiota. In this regard, probiotics have emerged as a promising therapy for infant FGIDs. In this study, we have investigated the probiotic potential of the strains Bifidobacterium longum KABP042 and Pediococcus pentosaceus KABP041 - isolated from healthy children’s feces - in the treatment of FGIDs. To this scope, genome sequences of both strains were obtained and subjected to in silico analyses. No virulence factors were detected for any strain and only the non-transferable erm(49) gene, which confers resistance to erythromycin and clindamycin, was identified in the genome of B. longum KABP042. Safety of both strains was confirmed by acute oral toxicity in rats. In vitro characterization revealed that the strains tolerate gastric and bile challenges and display a great adhesion capacity to human intestinal cells. The two strains mediate adhesion by different mechanisms and, when combined, synergically induce the expression of Caco-2 tight junction proteins. Moreover, growth inhibition experiments demonstrated the ability of the two strains alone and in combination to antagonize diverse Gram-negative and Gram-positive bacterial pathogens during sessile and planktonic growth. Pathogens’ inhibition was mostly mediated by the production of organic acids, but neutralization experiments strongly suggested the presence of additional antimicrobial compounds in probiotic culture supernatants such as the bacteriocin Lantibiotic B, whose gene was detected in the genome of B. longum KABP042. Finally, an exploratory, observational, pilot study involving 36 infants diagnosed with at least one FGID (infant colic and/or functional constipation) showed the probiotic formula was well tolerated and FGID severity was significantly reduced after 14 days of treatment with the 2 strains. Overall, this work provides evidence of the probiotic and synergic properties of strains B. longum KABP042 and P. pentosaceus KABP041, and of their potential to treat pediatric FGIDs.